Textbook outcome after major liver resection for primary and secondary liver tumors at specialized German hepatobiliary centers: analysis of the StuDoQ liver registry - Heil, Jan; Sliwinski, Svenja; D’Haese, Jan; Fangmann, Josef; Farkas, Stefan; Grützmann, Robert; Glanemann, Matthias; Kalff, Jörg C.; Mees, Sören T.; Mehrabi, Arianeb; Michalski, Christoph; Pratschke, Johann; et al. (Annals of surgical oncology, 2025)
Textbook outcome (TO) represents the most desirable outcome of surgical quality and care. This study examined the TO of cholangiocarcinoma (CCC), hepatocellular carcinoma (HCC), and colorectal liver metastasis (CRLM) from the StuDoQ liver registry as well as factors that may affect the TO.